THE RELATIONSHIP BETWEEN ACCOUNTING CONSERVATISM LEVEL AND THE AMOUNT OF BANK LOAN IN INDONESIAN STOCK EXCHANGE (IDX) COMPANIES FOR 2012 – 2014 PERIOD - Rivo Giovanni Lasmindar (CALYPTRA, 2018)
In today’s era financial statement is prepared to benefit several parties for a certain purpose. Thus, information in financial statement is not neutral containing information asymmetries. Conservatism principle in accounting emerges to give protections for the information users. Using banks institution as the financial statement users to see the relationship between accounting conservatism and the amount of bank loan – as their form of decision – in the companies listed in IDX for 2012 to 2014. This finding shows that accounting conservatism do not significantly affecting the amount of Bank Loan. However, the liquidities ratio and the cash flow from operating activities can be an indicator to the amount of Bank Loan possess by the companies.